2022
DOI: 10.3390/ijerph19148318
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Fundamental Motor Skills Proficiency in Children Aged 3–6 Years: A Systematic Review and Meta-Analysis

Abstract: The age range of 3–6 years is considered as a critical period in developing and learning fundamental motor skills (FMS). To make the formulation of future FMS guidance programs more targeted, we examined gender differences in children’s FMS proficiency using a meta-analysis. Structured electronic databases including PubMed, Scopus and Web of Science were systematically searched using key terms, and the Joanna Briggs Institute (JBI) was used to assess the quality of included literature. Finally, 38 articles (39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 82 publications
4
15
0
Order By: Relevance
“…The most recent meta-analytic review on the topic, 17 which covered children aged 3-6 years, found similar evidence to the current study with regard to skill patterning by sex. Other studies have shown that object control skills are typically better in boys, 17,[36][37][38] but 39 locomotor skills are less consistent in sex patterning. These inconsistencies could be attributed to the different protocols used, to individual variabilities, and to cultural differences.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The most recent meta-analytic review on the topic, 17 which covered children aged 3-6 years, found similar evidence to the current study with regard to skill patterning by sex. Other studies have shown that object control skills are typically better in boys, 17,[36][37][38] but 39 locomotor skills are less consistent in sex patterning. These inconsistencies could be attributed to the different protocols used, to individual variabilities, and to cultural differences.…”
Section: Discussionsupporting
confidence: 86%
“…For 3-5 years old, boys had higher object control raw scores than girls at the age of three , and four , and this difference increased at the age of 5 . The most recent meta-analytic review on the topic, 17 which covered children aged 3-6 years, found similar evidence to the current study with regard to skill patterning by sex. Other studies have shown that object control skills are typically better in boys, 17,[36][37][38] but 39 locomotor skills are less consistent in sex patterning.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…First is elementary student because in this phase, potential gross motoric growing rapidly (Burhaein, 2017). Second is boy because boys have better motoric movement than girls (Zheng et al, 2022). The last is experiencing congenital total visual impairment.…”
Section: Methodsmentioning
confidence: 99%